Reflejos culturales en la percepción: vocabulario del tacto en Teócrito (Minerva, 2019)
This study about the adjectives of wetness-dryness in Theocritus tries to show how a late author like Theocritus gathers literary and scientific traditions before him as a doctus poet. The study reveals in which way sensitive processes have great importance in order to contrast perceptive schemes in any culture. Moreover, the paper tries to apply to the semantic studies on ancient Greek language the knowledge from Psychology and Knowledge Philosophy.